Eco-Green Project, Social Entrepreneurship Learning : The Innovation Incubator Research in University Next ? - Gunawan Budi Santoso; Arif Julianto Sri Nugroho; Tukiyo Tukiyo (Cita Konsultindo Research Center, 2024)
This research has an urgency to form independent social entrepreneurs so as to produce graduates who are qualified, competitive and able to create innovations. The international relevance research show the succes entrepreneurs’s students in future depending on entrepreneuship learning method. The purpose of this research to develop learning tools for the Eco-green project through social entrepreneurial activities based on local wisdom values. The article descibes a new concept based on Theory of Planned Behavior enabling to serve as social entrepreneurship learning material for students which leads to the creation of superior graduates in the future. Participatory action research activities are expected to become a basis for model testing and needs analysis in developing a complete eco-green project learning model for social entrepreneurs. The research activity is in collaboration with the partners of the Abdurrahman Bin-Auf Klaten Islamic Boarding School the Klaten Regency, Environmental Service and leading waste bank business activists in Klaten Regency. The values ​​of local wisdom are included in the model test in the form of caring for the environment, religiosity, community, diversity and acceptance. The final results of the first phase of the research showed positive changes in the participants. Our method allows to improve that participatory action research activities are effective where the t-test before and after the activity is significantly different. The new method for efectiveness evaluation is confirmed by the calculation of the experiment research. Our method allows to improve students as drivers of the eco-green spirit are capable of being the initiators and motivators of the waste-bank business in their respective domiciles. New research improve the social entreperenurship learning method and can be used for entrepreneurship learning method for student in future